2017
DOI: 10.1038/s41598-017-17591-9
|View full text |Cite
|
Sign up to set email alerts
|

Dual-specificity phosphatase 5 acts as an anti-inflammatory regulator by inhibiting the ERK and NF-κB signaling pathways

Abstract: Although dual-specificity phosphatase 5 (DUSP5), which inactivates extracellular signal-regulated kinase (ERK), suppresses tumors in several types of cancer, its functional roles remain largely unknown. Here, we show that DUSP5 is induced during lipopolysaccharide (LPS)-mediated inflammation and inhibits nuclear factor-κB (NF-κB) activity. DUSP5 mRNA and protein expression increased transiently in LPS-stimulated RAW 264.7 cells and then returned to basal levels. DUSP5 overexpression in RAW 264.7 cells suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 50 publications
0
37
0
1
Order By: Relevance
“…In macrophages, DUSP5 expression was induced by the LPS stimulation of TLR4 and reduced cytokine production in RAW264.7 macrophages at the level of ERK1/2-dependent AP1 activation [72]. The stimulation of macrophages with the mycobacterial cord factor trehalose-6,6-dimycolate also upregulated DUSP5 expression, independent of the cord factor receptor Mincle (9).…”
Section: Dusp In Immunity and Infectionmentioning
confidence: 99%
“…In macrophages, DUSP5 expression was induced by the LPS stimulation of TLR4 and reduced cytokine production in RAW264.7 macrophages at the level of ERK1/2-dependent AP1 activation [72]. The stimulation of macrophages with the mycobacterial cord factor trehalose-6,6-dimycolate also upregulated DUSP5 expression, independent of the cord factor receptor Mincle (9).…”
Section: Dusp In Immunity and Infectionmentioning
confidence: 99%
“…Several lines of evidence have shown that ERK activation might activate NF-κB ( 42 , 43 ). Inactivation of both ERK1/2 and NF-κB pathways inhibits the level of TNF-α ( 44 ) and inflammation ( 45 , 46 ). Overproduction of TNF-α and IL-1β results in the injury in spinal cord and finally causes demyelination ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following assays were conducted as previously described by our laboratory [27, 28]. Lentiviral particles were used to deliver tetracycline-inducible recombinant DNA constructs.…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentrations of the lysates were measured by BCA protein assay kit (Bio-Rad, Hercules, CA). The lysates (10–20 µg protein) were separated on 4–20% SDS polyacrylamide mini-gels (Bio-Rad, Hercules, CA) and transferred to PVDF or nitrocellulose membrane followed by western blot analysis as described previously [27]. The antibodies used were as follows: mouse monoclonal anti-BRAF(V600E) (1:4000, Spring Bioscience, Pleasanton, CA), NRAS(Q61R) (1:2000, Abnova, Atlanta, GA), (SPRY4) anti-Sprouty4, NRAS, BRAF (1:1000, Santa Cruz Biotechnology, Dallas, TX), and mouse monoclonal anti-GAPDH (1:40,000, Abcam, Cambridge, MA) for 2 h, and horseradish peroxidase-conjugated secondary antibody (1:4000) for 1 h. Antigen–antibody complexes were detected by ECL enhanced chemiluminescence solution (Bio-Rad, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%